Method for structural modification of hollow nanotube carbon nitride and photocatalytic decomposition to produce hydrogen
By hydrothermal treatment and calcining melamine and aromatic small molecules, hollow nanotube carbon nitride is solved, the problem of low efficiency of graphite phase carbon nitride photocatalyst is improved, and the light absorption and carrier transmission performance of the photocatalyst is improved, so as to achieve It has efficient photocatalytic hydrogen production effect and is suitable for industrial applications.
Patent Information
- Application Number
- CN202411266279.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-09-11
AI Technical Summary
The existing graphite phase carbon nitride (g-C3N4) photocatalysts have low efficiency when decomposing water to prepare hydrogen, have high carrier recombination rate and small specific surface area, which limits their industrial application value.
By hydrothermal treatment of melamine and aromatic small molecules, supramolecular precursors are prepared, and modified hollow nanotube-shaped carbon nitride is obtained by calcining, thereby improving its light absorption performance and carrier transport performance.
It significantly enhances the absorption capacity of the photocatalyst in the visible light zone, reduces carrier recombination, improves the photocatalytic hydrogen production performance, and simplifies the preparation process, which is suitable for industrial large-scale production.
Smart Images

Figure CN118790960B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of hydrogen energy preparation, and in particular to a method for modifying the structure of hollow nano-tubular carbon nitride and producing hydrogen through photocatalytic decomposition. Background Art
[0002] Hydrogen energy has always been regarded as an ideal clean renewable energy source with high energy density, excellent combustion performance, easy storage and transportation, and no pollution. Using solar energy to photocatalytically decompose water to produce hydrogen is a clean energy technology that converts solar energy into hydrogen energy, and is expected to achieve a sustainable "hydrogen economy". Among them, the preparation of non-toxic, cheap, efficient and stable visible light photocatalysts is one of the keys to this technology.
[0003] The reaction principle of photocatalytic hydrogen production includes three main steps: the first is the generation of photogenerated carriers. When light irradiates the surface of the photocatalyst, the valence band electrons absorb photons with energy greater than the band gap energy and transition to the conduction band to become photogenerated electrons, while the valence band forms photogenerated holes. These electron-hole pairs are called photogenerated carriers. Photogenerated electrons have the ability to reduce and participate in the hydrogen evolution reaction, and photogenerated holes have the ability to oxidize and participate in the oxygen evolution reaction. The second step is the transfer of photogenerated carriers. Some photogenerated carriers migrate to the surface and participate in the reaction. Only photogenerated carriers that successfully migrate and do not recombine can effectively participate in the reaction. The last step is the redox reaction. After some photogenerated carriers migrate to the surface, they combine with substances in the solution and participate in the redox reaction. In the photocatalytic decomposition of water to produce hydrogen, photogenerated electrons combine with hydrogen ions in water to generate hydrogen, and photogenerated holes oxidize the sacrificial agent into organic matter. In the actual reaction, a series of intermediate products may be produced. To ensure the photocatalytic decomposition of water to produce hydrogen, the energy band structure of the photocatalyst needs to meet certain requirements so that the photogenerated electrons participate in the hydrogen evolution reaction and the photogenerated holes participate in the oxygen evolution reaction. The photocatalyst needs to absorb energy, and the band gap energy corresponding to the shortest wavelength of sunlight is 4.2 eV. According to the energy band structure of the photocatalyst, the band gap energy of the currently common photocatalysts is in the range of 1.23~4.2 eV.
[0004] Since the energy of sunlight is mainly concentrated in the visible light region, the preparation of photocatalysts with visible light response has always been a hot topic and focus of research. The graphite phase carbon nitride (g-C3N4) photocatalyst has a band gap width of about 2.7 eV, good acid, alkali, light and thermal stability, easy to control morphology and energy band, and can decompose water to produce hydrogen under visible light. It has been widely used in the field of photocatalysis. In addition, the raw materials for the preparation of g-C3N4 are abundant, the preparation method is simple, and the preparation cost is low, which has great application prospects and research value. However, the efficiency of g-C3N4 in decomposing water to produce hydrogen in the current research results cannot meet the requirements of industrial production, and it often shows low photocatalytic hydrogen production efficiency due to problems such as high carrier recombination rate and small specific surface area, which limits its potential application value. Summary of the invention
[0005] In order to overcome the problems existing in the related art, this specification provides a method for structural modification of hollow nanotubular carbon nitride and photocatalytic decomposition to produce hydrogen, so as to improve the photocatalytic hydrogen production performance of carbon nitride.
[0006] According to a first aspect of the present disclosure, there is provided a method for modifying a hollow nanotubular carbon nitride structure, comprising:
[0007] Melamine is mixed with aromatic small molecules and subjected to hydrothermal treatment to obtain a supramolecular precursor;
[0008] calcining the supramolecular precursor to obtain modified hollow nanotube carbon nitride;
[0009] Wherein, the molar percentage of the aromatic small molecules to the melamine is a, and a≥0;
[0010] The aromatic small molecule is selected from benzoic acid small molecules or halogen-containing benzoic acid small molecules.
[0011] In some exemplary embodiments of the present disclosure, the halogen contained in the halogen-containing benzoic acid small molecule is selected from chlorine and / or bromine.
[0012] In some exemplary embodiments of the present disclosure, the halogen-containing benzoic acid small molecule is selected from one of 2,5-dichlorobenzoic acid, 2,5-dibromobenzoic acid, and 2-bromo-5-chlorobenzoic acid.
[0013] In some exemplary embodiments of the present disclosure, 0<a≤10%.
[0014] In some exemplary embodiments of the present disclosure, the step of mixing melamine with aromatic small molecules and performing hydrothermal treatment to obtain a supramolecular precursor comprises:
[0015] Add the melamine to deionized water, heat and stir until the solid is completely dissolved to obtain a first solution;
[0016] Adding the aromatic small molecule to the first solution, heating and stirring until the solid is completely dissolved, to obtain a second solution;
[0017] The second solution is subjected to a hydrothermal reaction, and after the reaction is completed, the solution is filtered and dried to obtain the supramolecular precursor.
[0018] In some exemplary embodiments of the present disclosure, the heating temperature of the melamine in deionized water is 80° C.-95° C.
[0019] In some exemplary embodiments of the present disclosure, the hydrothermal reaction of the second solution is carried out in a hydrothermal kettle, and the hydrothermal kettle is placed in an external environment with a temperature of 175° C.-185° C., and the hydrothermal reaction time is 12 h-24 h.
[0020] In some exemplary embodiments of the present disclosure, the step of calcining the supramolecular precursor to obtain the modified hollow nanotubular carbon nitride comprises:
[0021] The supramolecular precursor is placed in a nitrogen tube furnace for calcination, and naturally cooled after calcination to obtain the hollow nano-tubular carbon nitride.
[0022] In some exemplary embodiments of the present disclosure, the calcination temperature is 500° C.-600° C., and the calcination time is 120 min-240 min;
[0023] The heating rate of the nitrogen tube furnace is 2°C min -1 -4℃ min -1 .
[0024] According to a second aspect of the present disclosure, a method for producing hydrogen by photocatalytic decomposition is provided, using the hollow nanotubular carbon nitride prepared by the method described in the first aspect as a photocatalyst.
[0025] The technical solution provided by the present disclosure may have the following beneficial effects:
[0026] The present disclosure provides a method for modifying the structure of hollow nano-tubular carbon nitride, which successfully prepares a supramolecular precursor by hydrothermal treatment of melamine and aromatic small molecules, and then obtains modified hollow nano-tubular carbon nitride by calcining the supramolecular precursor.
[0027] The modified carbon nitride has strong light absorption performance, and the absorption in the visible light region has been significantly enhanced. Secondly, the hollow nanotube structure is conducive to the effective separation and transmission of electrons and holes, thereby improving the carrier transmission performance, reducing the recombination of carriers, and improving the utilization efficiency of carriers in the photocatalytic process. In addition, the structurally modified carbon nitride exhibits excellent photocatalytic hydrogen production performance under visible light irradiation.
[0028] The method provided by the present invention can not only achieve the regulation of the structure and morphology of carbon nitride to form a hollow nanotube structure that is beneficial to improving the photocatalytic performance, but also is easy to operate, easy to mass produce, and has good repeatability, laying a foundation for industrial application.
[0029] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the specification and, together with the description, serve to explain the principles of the specification.
[0031] Figure 1 is the X-ray diffraction (XRD) pattern of different carbon nitrides.
[0032] Figure 2 These are infrared (FTIR) images of different carbon nitrides.
[0033] Figure 3 is the light absorption (UV-vis) graph of different carbon nitrides.
[0034] Figure 4 This is a scanning electron microscope (SEM) image of carbon nitride MCN-2.5ClBrBA prepared by adding 2-bromo-5-chlorobenzoic acid small molecules.
[0035] Figure 5 This is a transmission electron microscope (TEM) photograph of carbon nitride MCN-2.5ClBrBA prepared by adding 2-bromo-5-chlorobenzoic acid small molecules.
[0036] Figure 6 is the steady-state fluorescence spectrum (PL) diagram of different carbon nitrides.
[0037] Figure 7 This is a diagram of the visible light catalytic hydrogen production activity of different carbon nitrides.
[0038] Figure 8 This is a test chart of the visible light catalytic hydrogen production stability of MCN-2.5ClBrBA. DETAILED DESCRIPTION
[0039] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in many forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that this disclosure will be comprehensive and complete and will fully convey the concept of the example embodiments to those skilled in the art.
[0040] The present disclosure provides a method for modifying a hollow nanotube carbon nitride structure, comprising:
[0041] Step S100, mixing melamine and aromatic small molecules and performing hydrothermal treatment to obtain a supramolecular precursor;
[0042] Step S200, calcining the supramolecular precursor to obtain modified hollow nano-tubular carbon nitride.
[0043] The present disclosure provides a method for modifying the structure of hollow nano-tubular carbon nitride, which successfully prepares a supramolecular precursor by hydrothermal treatment of melamine and aromatic small molecules, and then obtains modified hollow nano-tubular carbon nitride by calcining the supramolecular precursor.
[0044] The modified carbon nitride has strong light absorption performance, and the absorption in the visible light region has been significantly enhanced. Secondly, the hollow nanotube structure is conducive to the effective separation and transmission of electrons and holes, thereby improving the carrier transmission performance, reducing the recombination of carriers, and improving the utilization efficiency of carriers in the photocatalytic process. In addition, the structurally modified carbon nitride exhibits excellent photocatalytic hydrogen production performance under visible light irradiation.
[0045] The method provided by the present invention can not only achieve the regulation of the structure and morphology of carbon nitride to form a hollow nanotube structure that is beneficial to improving the photocatalytic performance, but also is easy to operate, easy to mass produce, and has good repeatability, laying a foundation for industrial application.
[0046] The various steps of the method for modifying the hollow nanotube carbon nitride structure provided by the present disclosure will be described in detail below with reference to the accompanying drawings:
[0047] The present disclosure provides a method for modifying a hollow nano-tubular carbon nitride structure, comprising:
[0048] Step S100, mixing melamine and aromatic small molecules and performing hydrothermal treatment to obtain a supramolecular precursor;
[0049] Step S200, calcining the supramolecular precursor to obtain modified hollow nano-tubular carbon nitride.
[0050] Wherein, the molar percentage of the aromatic small molecules to the melamine is a, and a≥0;
[0051] The aromatic small molecule is selected from benzoic acid small molecules or halogen-containing benzoic acid small molecules.
[0052] In step S100, melamine ( ) can be in solid powder form. In the halogen-containing benzoic acid small molecule, the halogen can be selected from one or more of chlorine, bromine, and iodine, and the halogen on the benzoic acid can contain one or more. Preferably, the halogen contained in the halogen-containing benzoic acid small molecule is selected from chlorine and / or bromine.
[0053] Furthermore, the halogen-containing benzoic acid small molecule is selected from one of 2,5-dichlorobenzoic acid, 2,5-dibromobenzoic acid, and 2-bromo-5-chlorobenzoic acid.
[0054] Optionally, 0<a≤10%, and may specifically be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, but is not limited thereto.
[0055] It should be noted here that the hollow nanotubular carbon nitride provided by the present disclosure is also called graphite phase carbon nitride (g-C3N4).
[0056] In some embodiments of the present disclosure, step S100 includes:
[0057] Step S110, adding the melamine into deionized water and heating and stirring until the solid is completely dissolved to obtain a first solution;
[0058] Step S120, adding the aromatic small molecule to the first solution, heating and stirring until the solid is completely dissolved, to obtain a second solution;
[0059] Step S130, subjecting the second solution to a hydrothermal reaction, and after the reaction is completed, filtering and drying to obtain the supramolecular precursor.
[0060] In step S110, melamine and deionized water may be placed in a container and then transferred to an oil bath for heating and stirring for a period of time until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0061] In this step, the weight ratio of melamine to deionized water may be 1:15-25, the heating temperature may be 80°C-95°C, and the stirring time may be 20min-40min.
[0062] For example, 4.0 g of melamine and 80 mL of deionized water can be placed in a 250 mL conical flask, transferred to a stable 80°C-95°C oil bath, and heated and stirred for 30 minutes until the solid melamine is completely dissolved and the solution is clear and transparent.
[0063] In step S120, the molar percentage of the benzoic acid small molecule or the halogen-containing benzoic acid small molecule to the melamine is b, 0<b≤10%. In this step, after the benzoic acid or the halogen-containing benzoic acid small molecule is added to the first solution, it can be stirred for 60min-90min until the solid powder is completely dissolved.
[0064] In step S130, the hydrothermal reaction of the second solution is carried out in a hydrothermal kettle, and the hydrothermal kettle is placed in an external environment with a temperature of 175°C-185°C, specifically 175°C, 176°C, 177°C, 178°C, 179°C, 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, but not limited thereto. The hydrothermal reaction time is 12h-24h, specifically 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h, 21h, 22h, 23h, 24h, but not limited thereto.
[0065] In this step, when the second solution is large in amount, the second solution can be divided into different hydrothermal kettles in equal amounts, and the specifications of the hydrothermal kettles can be selected according to actual needs.
[0066] For example, the second solution is loaded into the inner lining of the hydrothermal kettle, and after tightening the outer shell of the hydrothermal kettle, it is placed in a 180°C oven for reaction for 12h-24h. After the hydrothermal kettle is cooled naturally, the obtained product is filtered and washed with deionized water for multiple times, and the solid is retained and dried in a vacuum oven at 60°C for 8h to finally obtain supramolecular precursors doped with different small molecules.
[0067] In some embodiments, step S200 includes:
[0068] The supramolecular precursor is placed in a nitrogen tube furnace for calcination, and naturally cooled after calcination to obtain the hollow nano-tubular carbon nitride.
[0069] The calcination temperature is 500°C-600°C, the calcination time is 120min-240min, and the heating rate of the nitrogen tubular furnace is 2°C min -1 -4℃ min -1 .
[0070] For example, 1 g of supramolecular precursor was weighed and spread in an ark, and then placed in a nitrogen tube furnace for calcination (heating rate was 3 °C min -1 ) is kept at 500°C-600°C for 120min-240min and then naturally cooled, and then the sample is transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotubular carbon nitride modified with small molecules.
[0071] The hollow nanotube carbon nitride obtained in the present disclosure can be used for photocatalytic decomposition to produce hydrogen.
[0072] The present disclosure also provides a method for producing hydrogen by photocatalytic decomposition, using the hollow nanotube carbon nitride prepared by the above method as a photocatalyst. The method comprises:
[0073] The hollow nanotube carbon nitride obtained by the above method is used as a photocatalyst, a triethanolamine aqueous solution is used as a sacrificial agent, and a hexahydrate chloroplatinic acid aqueous solution is added for light irradiation.
[0074] Wherein, an inert gas is introduced into the reactor before illumination to remove oxygen in the system.
[0075] The weight ratio of the hollow nano-tubular carbon nitride to the triethanolamine aqueous solution and the hexahydrate chloroplatinic acid aqueous solution is 20:5-200:0.2-0.4.
[0076] The triethanolamine content in the triethanolamine aqueous solution is 10 vol%-20 vol%; the platinum content in the hexahydrate chloroplatinic acid aqueous solution is 0.0005 g / mL-0.001 g / mL.
[0077] For example, methods for producing hydrogen by photocatalytic decomposition include:
[0078] (1) In a reactor with a volume of 250 mL, 20.0 mg to 100.0 mg of the small molecule-modified hollow nanotubular carbon nitride prepared by the above method was added as a photocatalyst, and a total volume of 80 mL of an aqueous solution with a triethanolamine content of 10 vol% to 20 vol% was added as a sacrificial agent; and 0.286 mL to 1.430 mL of an aqueous solution of chloroplatinic acid hexahydrate with a platinum content of 0.0007 g / mL was added;
[0079] (2) Before irradiation, argon gas was purged into the reactor for 15 min to remove oxygen from the system;
[0080] (3) Turn on the magnetic stirrer and the xenon lamp.
[0081] The present disclosure will be described below with reference to specific embodiments and accompanying drawings.
[0082] Example 1
[0083] (1) Weigh 4.0 g of melamine and 80 mL of deionized water into a 250 mL conical flask, transfer to a stable 95°C oil bath, heat and stir for 30 min until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0084] The first solution was placed in a 100 mL hydrothermal autoclave liner, and after tightening the hydrothermal autoclave shell, it was placed in a 180°C oven for reaction for 24 hours. After the hydrothermal autoclave was cooled naturally, the obtained product was filtered and washed with deionized water several times, and the solid was retained and dried in a vacuum oven at 60°C for 8 hours to finally obtain a supramolecular precursor.
[0085] (2) Weigh 1 g of supramolecular precursor and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min-1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotube carbon nitride.
[0086] (3) The hollow nanotube carbon nitride prepared in step (2) is subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0087] In a 250 mL reactor, add 20.0 mg of hollow nanotube carbon nitride photocatalyst, add 80 mL of a 10 vol% triethanolamine aqueous solution as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge the reactor with argon for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0088] Example 2
[0089] (1) Weigh 4.0 g of melamine and 80 mL of deionized water into a 250 mL conical flask, transfer to a stable 95°C oil bath, heat and stir for 30 min until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0090] A certain amount of benzoic acid (accounting for 2.5% of the molar percentage of melamine) was weighed and added to the first solution, and heated and stirred for 60 minutes until the solid powder was completely dissolved to obtain a second solution.
[0091] The second solution was placed in a 100 mL hydrothermal autoclave liner, and after tightening the hydrothermal autoclave shell, it was placed in a 180°C oven for reaction for 24 hours. After the hydrothermal autoclave was cooled naturally, the obtained product was filtered and washed with deionized water for multiple times, and the solid was retained and dried in a vacuum oven at 60°C for 8 hours to finally obtain a supramolecular precursor doped with a benzoic acid small molecule.
[0092] (2) Weigh 1 g of supramolecular precursor and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min -1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotube carbon nitride modified with benzoic acid small molecules.
[0093] (3) The hollow nanotube carbon nitride modified with the benzoic acid small molecule prepared in step (2) was subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0094] In a 250 mL reactor, add 20.0 mg of hollow nanotube carbon nitride photocatalyst modified with benzoic acid small molecules, add 80 mL of a 10 vol% aqueous solution of triethanolamine as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge the reactor with argon for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0095] Example 3
[0096] (1) Weigh 4.0 g of melamine and 80 mL of deionized water into a 250 mL conical flask, transfer to a stable 95°C oil bath, heat and stir for 30 min until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0097] A certain amount (accounting for 2.5% of the molar percentage of melamine) of 2,5-dichlorobenzoic acid was weighed and added to the first solution, and heated and stirred for 60 minutes until the solid powder was completely dissolved to obtain a second solution.
[0098] The second solution was placed in a 100 mL hydrothermal autoclave liner, and after tightening the hydrothermal autoclave shell, it was placed in a 180°C oven for reaction for 24 h. After the hydrothermal autoclave was cooled naturally, the obtained product was filtered and washed with deionized water several times, and the solid was retained and dried in a vacuum oven at 60°C for 8 h to finally obtain a supramolecular precursor doped with a small molecule of 2,5-dichlorobenzoic acid.
[0099] (2) Weigh 1 g of supramolecular precursor and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min -1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotube carbon nitride modified with 2,5-dichlorobenzoic acid small molecules.
[0100] (3) The hollow nanotube carbon nitride modified with the 2,5-dichlorobenzoic acid small molecule prepared in step (2) was subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0101] In a 250 mL reactor, add 20.0 mg of the hollow nanotube carbon nitride photocatalyst modified by the small molecule of 2,5-dichlorobenzoic acid, add 80 mL of a 10 vol% aqueous solution of triethanolamine as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge the reactor with argon for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0102] Example 4
[0103] (1) Weigh 4.0 g of melamine and 80 mL of deionized water into a 250 mL conical flask, transfer to a stable 95°C oil bath, heat and stir for 30 min until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0104] A certain amount (accounting for 10% of the molar percentage of melamine) of 2,5-dibromobenzoic acid was weighed and added to the first solution, and heated and stirred for 60 minutes until the solid powder was completely dissolved to obtain a second solution.
[0105] The second solution was placed in a 100 mL hydrothermal autoclave liner, and after tightening the hydrothermal autoclave shell, it was placed in a 180°C oven for reaction for 24 h. After the hydrothermal autoclave was cooled naturally, the obtained product was filtered and washed with deionized water several times, and the solid was retained and dried in a vacuum oven at 60°C for 8 h to finally obtain a supramolecular precursor doped with a small molecule of 2,5-dibromobenzoic acid.
[0106] (2) Weigh 1 g of supramolecular precursor and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min -1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotube carbon nitride modified with 2,5-dibromobenzoic acid small molecules.
[0107] (3) The hollow nanotube carbon nitride modified with the 2,5-dibromobenzoic acid small molecule prepared in step (2) was subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0108] In a 250 mL reactor, add 20.0 mg of the hollow nanotube carbon nitride photocatalyst modified by the small molecule of 2,5-dibromobenzoic acid, add 80 mL of a 10 vol% aqueous solution of triethanolamine as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge the reactor with argon for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0109] Example 5
[0110] (1) Weigh 4.0 g of melamine and 80 mL of deionized water into a 250 mL conical flask, transfer to a stable 95°C oil bath, heat and stir for 30 min until the solid melamine is completely dissolved to obtain a first solution, which is clear and transparent.
[0111] A certain amount (accounting for 2.5% of the molar percentage of melamine) of 2-bromo-5-chlorobenzoic acid was weighed and added to the first solution, and heated and stirred for 60 minutes until the solid powder was completely dissolved to obtain a second solution.
[0112] The second solution was placed in a 100 mL hydrothermal autoclave liner, and after tightening the hydrothermal autoclave shell, it was placed in a 180°C oven for reaction for 24 h. After the hydrothermal autoclave was cooled naturally, the obtained product was filtered and washed with deionized water several times, and the solid was retained and dried in a vacuum oven at 60°C for 8 h to finally obtain a supramolecular precursor doped with a small molecule of 2-bromo-5-chlorobenzoic acid.
[0113] (2) Weigh 1 g of supramolecular precursor and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min -1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain hollow nanotube carbon nitride modified with 2-bromo-5-chlorobenzoic acid small molecules.
[0114] (3) The hollow nanotube carbon nitride modified with the 2-bromo-5-chlorobenzoic acid small molecule prepared in step (2) was subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0115] In a 250 mL reactor, add 20.0 mg of the hollow nanotube carbon nitride photocatalyst modified by the small molecule of 2-bromo-5-chlorobenzoic acid, add 80 mL of a 10 vol% aqueous solution of triethanolamine as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge the reactor with argon for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0116] Comparative Example
[0117] (1) Weigh 1 g of melamine and spread it flat in an ark, then place it in a nitrogen tube furnace for calcination (heating rate: 3 °C min -1 ) was kept at 550°C for 240 min and then naturally cooled. The sample was then transferred to a dry place at room temperature and sealed for storage to obtain carbon nitride.
[0118] (2) The carbon nitride prepared in step (1) is subjected to a photocatalytic water decomposition hydrogen production test. The specific steps are as follows:
[0119] Add 20.0 mg of carbon nitride photocatalyst to a 250 mL reactor, add 80 mL of a 10 vol% triethanolamine aqueous solution as a sacrificial agent, and add 0.286 mL of a hexahydrate chloroplatinic acid aqueous solution with a platinum content of 0.0007 g / mL. Purge argon into the reactor for 15 minutes to remove oxygen from the system. Turn on the magnetic stirrer and the xenon lamp.
[0120] In the above embodiments and comparative examples, the hollow nanotubular carbon nitride obtained by direct calcination of melamine is named CN. The hollow nanotubular carbon nitride obtained by calcination after hydrothermal treatment of melamine is named MCN. The hollow nanotubular carbon nitride obtained by calcination after hydrothermal treatment of melamine and benzoic acid is named MCN-2.5BA. The hollow nanotubular carbon nitride obtained by calcination after hydrothermal treatment of melamine and 2,5-dichlorobenzoic acid is named MCN-2.5ClBA. The hollow nanotubular carbon nitride obtained by calcination after hydrothermal treatment of melamine and 2,5-dibromobenzoic acid is named MCN-2.5BrBA. The hollow nanotubular carbon nitride obtained by calcination after hydrothermal treatment of melamine and 2-bromo-5-chlorobenzoic acid is named MCN-2.5ClBrBA.
[0121] The X-ray diffraction (XRD) graph, infrared (FTIR) graph, light absorption (UV-vis) graph, steady-state fluorescence spectrum (PL) graph, and visible light photocatalytic hydrogen production activity graph of the carbon nitride prepared in each embodiment and comparative example were obtained.
[0122] In the present disclosure, the XRD instrument used is an X'Pert PROMPD X-ray diffractometer from PANalytical, with a 2θ scanning range of 5°-60°; the Fourier transform infrared spectrometer used is a Vextex70 model from Bruker, Germany, with an infrared light wave number range of 4000 -1 - 400 cm -1 The UV-vis instrument used was a Bayer Cary5000 UV-visible near-infrared spectrophotometer with a test wavelength range of 300 nm-800 nm; the photoluminescence spectrometer used was the FLS1000 model from Edinburgh, UK.
[0123] The visible light catalytic hydrogen production activity was obtained by gas chromatography: at every 1 h time interval of the reaction, a microsyringe was used to puncture the silicone plug and enter the gas space above the reaction bottle, 200 μL of gas was extracted and input into a gas chromatograph with a TDX-01 molecular sieve column to measure the hydrogen content. The sampling and air intake operation was repeated three times for each measurement and the average value was taken. The data obtained was used to obtain the hydrogen yield using the formula corresponding to the chromatography.
[0124] As shown in the attached figure, Figure 1 The X-ray diffraction (XRD) diagrams of different carbon nitrides show that the carbon nitride sample CN directly calcined with melamine shows the characteristic peaks of typical graphite phase carbon nitride (g-C3N4). When melamine is hydrothermally treated alone and hydrothermally treated with benzoic acid, 2,5-dichlorobenzoic acid, 2,5-dibromobenzoic acid and 2-bromo-5-chlorobenzoic acid, the intensity of the characteristic peak of the (100) crystal plane of the calcined carbon nitride is significantly reduced. This indicates that the long-range ordered structure of the heptazine ring unit structure inside the carbon nitride is destroyed and there are a large number of defects in the structure of g-C3N4.
[0125] Figure 2 These are the infrared (FTIR) images of different carbon nitrides. All carbon nitride samples show the characteristic peaks of typical graphite phase carbon nitride (g-C3N4).
[0126] Figure 3 This is the light absorption (UV-vis) graph of different carbon nitrides. Compared with other carbon nitrides, the carbon nitrides MCN-2.5BrBA and MCN-2.5ClBrBA prepared by adding 2,5-dibromobenzoic acid and 2-bromo-5-chlorobenzoic acid small molecules have the widest light absorption range, indicating that the Br element plays a major role in improving the light absorption capacity.
[0127] Figure 6 The steady-state fluorescence spectra (PL) of different carbon nitrides are shown in Figure 1. The carbon nitride CN obtained by direct calcination of melamine has the strongest PL peak, indicating that its carrier recombination is the most serious; the PL of the carbon nitride MCN obtained by hydrothermal treatment of melamine and then calcination is significantly weakened. As benzoic acid, 2,5-dichlorobenzoic acid, 2,5-dibromobenzoic acid and 2-bromo-5-chlorobenzoic acid are introduced in the hydrothermal process, the PL intensity of the obtained carbon nitride is further weakened. When the introduced small molecule is 2-bromo-5-chlorobenzoic acid, the corresponding carbon nitride MCN-2.5ClBrBA has the weakest PL peak, indicating that its carrier recombination is suppressed to the maximum extent and the utilization rate of photogenerated electrons is improved to the maximum extent. Therefore, it is shown that the introduction of benzoic acid small molecules containing both Cl and Br elements in melamine can more effectively suppress the recombination of carriers than the introduction of benzoic acid small molecules that do not contain or contain only one of the elements.
[0128] Figure 7 The photocatalytic hydrogen production activity of different carbon nitrides under visible light is shown in Figure 2. The photocatalytic hydrogen production performance of carbon nitride MCN-2.5ClBrBA prepared by introducing 2-bromo-5-chlorobenzoic acid small molecules is significantly higher than that of other carbon nitrides, and the hydrogen production rate can reach 839.0 μmolh -1 g -1 .
[0129] also, Figure 4This is a scanning electron microscope (SEM) photo of carbon nitride MCN-2.5ClBrBA prepared by adding 2-bromo-5-chlorobenzoic acid small molecules. From the shape of the sample cross section in the figure, the hollow nanotube structure of g-C3N4 can be clearly seen. The SEM equipment used in this disclosure is the Quanta Master 40 model of PTI Company in the United States.
[0130] Figure 5 This is a transmission electron microscope (TEM) photo of carbon nitride MCN-2.5ClBrBA prepared by adding 2-bromo-5-chlorobenzoic acid small molecules. It can be seen from the figure that the top and bottom colors are slightly darker, indicating that this part of the material is stacked, while the middle color is slightly lighter, and the broken cross section on the left clearly shows that the color of the single layer is lighter, which can further prove the hollow nanotube shape of g-C3N4. The TEM equipment used in this disclosure is the Japanese JEOL JEM-2100Plus model.
[0131] Figure 8 This is a test chart of the stability of MCN-2.5ClBrBA in visible light catalytic hydrogen production, which shows that the catalyst has good stability. The test method is: at every 1 h time interval of the reaction, use a micro syringe to puncture the silicone plug to enter the gas space above the reaction bottle, extract 200 μL of gas, and input it into the gas chromatograph of the TDX-01 molecular sieve column to measure the hydrogen content. The sampling and gas inlet operation is repeated three times for each measurement to take the average value, and the obtained data is used to obtain the hydrogen yield through the formula corresponding to the chromatogram; every 6 hours after the start of the reaction, the reaction bottle is re-purged with argon to verify the stability of the catalyst in this reaction system.
[0132] In the above embodiment, the photocatalytic hydrogen production performance of carbon nitride prepared by 2-bromo-5-chlorobenzoic acid and melamine is much higher than that of carbon nitride prepared by other methods, and the photocatalytic hydrogen production activity under visible light (λ≥400 nm) is 839 μmol h -1 g -1 (Loaded Pt co-catalyst). This indicates that the introduction of bromine and chlorine halogen elements into benzoic acid small molecules can more effectively improve light absorption performance and carrier utilization than the introduction of a single halogen element or benzoic acid small molecules without halogen elements, thereby improving the photocatalytic hydrogen production performance.
[0133] It should be noted that, although the steps of the method for forming the structure in the present disclosure are described in a specific order in the drawings, this does not require or imply that the steps must be performed in this specific order, or that all the steps shown must be performed to achieve the desired results. Additionally or alternatively, some steps may be omitted, multiple steps may be combined into one step, and / or one step may be decomposed into multiple steps, etc.
[0134] Those skilled in the art will readily appreciate other embodiments of the present disclosure after considering the specification and practicing the invention disclosed herein. This application is intended to cover any modification, use or adaptation of the present disclosure, which follows the general principles of the present disclosure and includes common knowledge or customary techniques in the art that are not disclosed in the present disclosure. The specification and examples are intended to be exemplary only, and the true scope and spirit of the present disclosure are indicated by the appended claims.
Claims
1. A method for modifying a hollow nanotube carbon nitride structure, characterized in that: include: Add melamine to deionized water, heat and stir until the solid is completely dissolved to obtain a first solution; Adding the aromatic small molecule to the first solution, heating and stirring until the solid is completely dissolved, to obtain a second solution; The second solution is subjected to a hydrothermal reaction, and after the reaction is completed, the solution is filtered and dried to obtain a supramolecular precursor; calcining the supramolecular precursor to obtain modified hollow nanotube carbon nitride; The weight ratio of melamine to deionized water is 1:15-25, the heating temperature of melamine in deionized water is 80°C-95°C, and the molar percentage of the aromatic small molecules in the melamine is a, 0<a≤10%; The aromatic small molecules are selected from halogen-containing benzoic acid small molecules, and the halogen contained in the halogen-containing benzoic acid small molecules is selected from chlorine and / or bromine.
2. The method according to claim 1, characterized in that The halogen-containing benzoic acid small molecule is selected from one of 2,5-dichlorobenzoic acid, 2,5-dibromobenzoic acid, and 2-bromo-5-chlorobenzoic acid.
3. The method according to claim 1, characterized in that The hydrothermal reaction of the second solution is carried out in a hydrothermal kettle, and the hydrothermal kettle is placed in an external environment with a temperature of 175° C.-185° C., and the hydrothermal reaction time is 12 h-24 h.
4. The method according to claim 1, characterized in that: The step of calcining the supramolecular precursor to obtain the modified hollow nano-tubular carbon nitride comprises: The supramolecular precursor is placed in a nitrogen tube furnace for calcination, and naturally cooled after calcination to obtain the hollow nano-tubular carbon nitride.
5. The method according to claim 4, characterized in that The calcination temperature is 500°C-600°C, and the calcination time is 120min-240min; The heating rate of the nitrogen tube furnace is 2°C min -1 -4℃ min -1 .
6. A method for producing hydrogen by photocatalytic decomposition, characterized in that: The hollow nanotube carbon nitride prepared by the method according to any one of claims 1 to 5 is used as a photocatalyst.
Citation Information
Patent Citations
Batch preparation method of porous carbon nitride material under assistance of organic carboxylic acid
CN105664835A
Modification method of graphite-like phase carbon nitride
CN114345388A